2022
DOI: 10.3390/jcm11113099
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Heparin in COVID-19: An Update after Two Years of Pandemics

Abstract: Coronavirus disease 2019 (COVID-19) is associated with an increased risk of venous thromboembolism (VTE) and coagulopathy, especially in critically ill patients. Endothelial damage induced by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is emerging as a crucial pathogenetic mechanism for the development of complications in an acute phase of the illness and for several postdischarge sequalae. Heparin has been shown to have a positive impact on COVID-19 due to its anticoagulant function. Moreover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 83 publications
0
15
0
Order By: Relevance
“… 4 , 6 These observations have generated interest in developing heparin as a therapeutic for SARS-CoV-2 infections. 5 , 15 , 16 , 38 , 39 Its use is, however, complicated by the structural heterogeneity and the risk of causing bleeding and thrombocytopenia. Therefore, there is an urgent need to develop well-defined heparin mimetics that can potently inhibit viral cell binding with reduced side effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 4 , 6 These observations have generated interest in developing heparin as a therapeutic for SARS-CoV-2 infections. 5 , 15 , 16 , 38 , 39 Its use is, however, complicated by the structural heterogeneity and the risk of causing bleeding and thrombocytopenia. Therefore, there is an urgent need to develop well-defined heparin mimetics that can potently inhibit viral cell binding with reduced side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutics may also reduce the prevalence of long-covid, which is associated with both hospitalized patients and those with mild or moderate disease. Earlier studies have demonstrated that SARS-CoV-2 employs HS for initial cell attachment and enzymatic removal of HS resulted in a very substantial reduction in cell binding and infectivity. , These observations have generated interest in developing heparin as a therapeutic for SARS-CoV-2 infections. ,,,, Its use is, however, complicated by the structural heterogeneity and the risk of causing bleeding and thrombocytopenia. Therefore, there is an urgent need to develop well-defined heparin mimetics that can potently inhibit viral cell binding with reduced side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Of biological relevance, either possibility suggests the application of heparan sulphate mimetics as anti-viral therapies. Indeed, soluble GAGs, especially heparin mimetics, have been used as competitive inhibitors to block Coronavirus infection [13][14][15] . Of relevance, the LMW-DS used in this study, ILB®, acts as a soluble heparin mimetic that can offer a competitive binding site for heparin-binding moieties, thereby preventing receptor interactions 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, Mangiafico and co-workers [19] reviewed the pathophysiology of vascular damage and the hypercoagulative state related to SARS-CoV-2 infection and the role of heparin in various COVID-19 clinical settings according to the most recent evidence [20][21][22][23][24]. Authors concluded that the prophylactic dose of heparin is recommended in all hospitalized patients unless contraindicated, while the therapeutic dose could be considered in nonpregnant patients requiring low-flow supplemental oxygen, with increased D-dimer levels and low bleeding risk [25][26][27].…”
mentioning
confidence: 97%
“…In the last two years, the new coronavirus has afflicted the whole world causing a pandemic burdened by high morbidity and mortality [1]. Over recent months, increasing evidence has been brought to light that venous thromboembolism (VTE) was a frequent complication that adversely affected the clinical course of the coronavirus disease 2019 (COVID- 19), especially in the most severe cases [2]. Consequently, numerous researchers around the world have focused efforts on identifying the underlying etiopathogenetic mechanisms of vascular involvement in COVID-19 and on potential therapies that can improve the outcome on these patients.…”
mentioning
confidence: 99%